Content Analysis of English Language Teaching Materials in The Food and Beverage Industry - Abdul Syahid; Aulia Rahmi; Nuralisa Nuralisa; Wafa Qaulan Syahida; Rizki Hasanah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This article discusses Content Analysis of English Language Teaching Materials in the Food and Beverage Industry. This research method uses descriptive research method. The results showed that the book "English for Food and Beverages" has 104 pages with 4 chapters. Used by Buleleng Seamen Alliance College, the focus is on the combination of speaking and reading skills for students who serve tourists in hotels or restaurants. The research also looked at the suitability of the tasks and materials with Burhan Nurgiantoro's criteria. Content analysis of English language teaching materials in the food and beverage industry is important to ensure that they meet industry needs, improve language and communication skills, and support professional development. Effective teaching materials can help learners in the hospitality and tourism industry to succeed in their careers. In addition, the use of appropriate evaluation criteria, such as those proposed by Burhan Nurgiantoro, can help in assessing the quality of tasks and materials in textbooks.